Determinants analysis of change-of-direction ability in elite soccer players - Chaouachi, A.; Manzi, V.; Chaalali, A.; Wong, D. P.; Chamari, K.; Castagna, C. (The Journal of Strength and Conditioning Research, 2012)
In this study, we examined the components of 2 change-of-direction (COD) ability (CODA) tests in elite-level male soccer players (n = 23, age 19 ± 1 years, height 181 ± 5.7 cm, body mass 73.2 ± 4.1 kg, % body fat 11 ± 2.4). As CODA paradigms, the T-test and 5-m shuttle run-sprint (5mSS) test assumed as describing the opposing ends of the COD complexity in soccer (i.e., general and specific tests, respectively) were considered. Results showed that the anthropometric and muscular performance variables were able to account for ~45% (p < 0.04) of the common variance of CODA. The T-test performance was explained by 8 variables (adjusted R2 = 0.45, p = 0.026), with 5mSS, height, knee extensors isokinetic concentric strength at 60°·per second, and right-to-left knee extensors eccentric strength deficit reaching a level of significance in the provided model (p kleiner/gleich 0.02). The best-fitting equation for 5mSS performance included 10 variables (adjusted R2 = 0.48, p = 0.036) of which T-test performance, height, percentage of body fat, and peak power during the countermovement jump resulted significantly affecting the common shared variance (p ? 0.03). This study finding showed that the affecting variables of CODA differ according to the test characteristics. Furthermore, the magnitude of the reported associations suggests that currently CODA should be regarded mainly as a task-specific fitness attribute. Further studies are warranted to detect more relevant performance variables to describe CODA. Meanwhile, soccer coaches and fitness trainers are advised to improve players' CODA using training drills that mimic crucial match actions.